THE TOTAL POLYPHENOLIC CONTENT AND ANTIOXIDANT PROPERTIES OF VARIOUS HONEY AND SUGARS - Chaiyasut, Chaiyavat; Kesika, Periyanaina; Peerajan, Sartjin; Sivamaruthi, Bhagavathi Sundaram (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Honey and sugars are rich in polyphenols and known for several health benefits. The quality of the honey varied on the floral source and geographical region. The sugar quality depends on the processing and source. The study aimed to evaluate the total polyphenolic content and antioxidant properties of selected Thai honey and sugar samples. Methods: Total polyphenol content and antioxidant properties were determined by the colorimetric method, and 2, 2′-azino-bis-3-ethylbenzthiazoline- 6-sulfonic acid, ferric reducing antioxidant potential (FRAP), and ferrous ion-chelating assays, respectively. Results: The honey from Eupatorium odoratum Linn (HEO) (0.75 mg gallic acid equivalent/ml of sample), and meal cane sugar (MCS) (4.13 mg gallic acid equivalent/g of sample) exhibited higher polyphenol content among the honey, and sugar samples, respectively. The refined sugar (RS) showed least phenolic content (0.02 mg gallic acid equivalent/g of sample) when compared to all tested sugars and honey samples. HEO exhibited high Trolox equivalent antioxidant capacity (TEAC; 235.93 mg TEAC per ml sample) among the honey samples. Among the sugars, MCS showed high TEAC (3891.22 mg TEAC per g sample). The honey from Nephelium lappaceum Linn and HEO has superior FRAP value and chelating power, respectively. The RS was least in total antioxidant capacity, FRAP, and chelating power. Conclusion: The HEO, and MCS and palm sugars are harbored with phenolic content and antioxidants. The refining process drastically diminished the quality of the sugar. The information may help to choose best carbon source for the preparation of fermented beverages with improved functional properties.